Foreign Body in Paranasal Sinus: A Late Clinical Presentation - Francisco Monteiro; Pedro Oliveira; Artur Condé (Case Reports in Otolaryngology)
The occurrence of foreign bodies in paranasal sinuses is extremely rare. The symptoms are vague and usually discovered after extra/intracranial complications. They may, therefore, go unnoticed if there isn’t a strong clinical suspicion. We present a clinical case of a 64-year-old woman with a paranasal sinus microsurgery history more than 30 years ago, who presented with headache and purulent rhinorrhea. A glass tubular structure was discovered in the ethmoid complex. She underwent functional endoscopic sinus surgery. Since glass is an inert material that doesn’t cause foreign body reaction, the patient may not present any symptom or sign. However, if there is obstruction in the drainage of the ostiomeatal complex, it can manifest itself as rhinosinusitis, which we believe happened in our case. To the best of our knowledge, this is probably the first reported case of a glass removed from the ethmoidal sinuses, diagnosed with more than 30 years of evolution.